The predictive value of the urinary iodine-to-creatine ratio in spot samples for the estimation of 24-hour urinary iodine excretion in adult non-pregnant women - Chudek, Jerzy; Fryżewska, Joanna; Kocełak, Piotr; Owczarek, Aleksander J.; Mikuła, Piotr; Chudek, Anna; Staniszewska-Mróz, Joanna; Winder, Mateusz; Olszanecka-Glinianowicz, Magdalena; Handzlik, Gabriela A. (Frontiers in Endocrinology, 2025)
ObjectiveThe study aimed to compare iodine-to-creatinine ratios in morning spot samples with 24-hour iodine excretion, serving as the reference standard in adult non-pregnant women. The additional objective was to examine the accuracy of the iodine-to-creatinine ratio in morning spot samples for assessing iodine intake.MethodsA cross-sectional, observational study included 49 non-pregnant adult women undergoing endocrine evaluation for adrenal incidentalomas in a hospital setting. Iodine and creatinine concentrations were measured in 24-hour collections and morning spot urine samples. The cut-off value for iodine deficiency in the 24-hour iodine excretion, based on iodine/creatinine in the urine spot sample, was assessed based on the ROC curve analysis.ResultsThe iodine-to-creatinine ratio in a morning spot urine sample correlated significantly with 24-hour urinary iodine excretion (R = 0.196; p = 0.002), unlike iodine concentration in the urine spot sample. Sufficient urinary iodine excretion (≥150 µg/day) was found in only 16.3% of participants, while iodine deficiency (<100 µg/day) was observed in 55.1%. The iodine-to-creatinine ratio cut-off of 73 µg/g identified iodine deficiency with 66.7% sensitivity and 72.7% specificity. However, its ability to detect mild insufficiency was limited. All cases of moderate deficiency were correctly classified.ConclusionsIodine to creatine ratio in morning spot urine sample modestly reflects 24-hour iodine urinary excretion but more accurately that iodine concentration alone. A cut-off value of 73 μg/g offers moderate diagnostic performance. A daily iodine intake of 100 µg may be sufficient to prevent its deficiency, suggesting reconsideration of current recommendations for iodine intake.